Alterações induzidas pela seca na absorção de nitrogênio, fósforo e potássio, e as relações com a tolerância da cana-de-açúcar ao deficit hídrico - da Silva, Thais Ramos [UNESP]; Cazetta, Jairo Osvaldo [UNESP]; Carlin, Samira Domingues; Telles, Bruna Robiati [UNESP] (FapUNIFESP (SciELO), 2017)
Although there are evidences that the proper supply of mineral nutrients to plants relieves water stress, little is known on the approach of how the drought affects the absorption and accumulation of nutrients by distinct sugar cane genotypes, or in different parts of a same plant. Thus, the objective of this study was to determine the content and accumulation of N, P and K in the aerial part of plant from three genotypes of sugar cane, submitted to three water potentials in the soil, and check the relationship of these variables with the tolerance of plants to prolonged drought. In order to access this objective, an experiment under greenhouse conditions, comprised by a fatorial 3 × 3, in a randomized block design, and four replicates was carried out. After 90 days from treatment imposition, the plant transpiration rate, plant dry mass, concentration of N, P and K were determined in leaves and culms, as well as in total plant shoot were measured. It was found that tolerance to drought in sugar cane is related to higher levels of N and K in the leaves and stems, and larger accumulations of K and P in the plant shoot. There is high positive correlations among accumulation of N, P and K in the plant shoot and dry matter production by plants submitted to drought. There are intermediate correlations among plant transpiration and nutrient uptake by plants under drought. Plants of the genotype SP81-3250 are more tolerante to prolonged drought, than the RB855453 and IACSP95-5000 plants.
Drought-induced alterations in the uptake of nitrogen, phosphorus and potassium, and the relation with drought tolerance in sugar cane
Keywords: Mineral nutrition; Plant growth; Saccharum officinarum L; Soil water potentials; Water limitations